HUBUNGAN MINAT MENJADI GURU DENGAN KESIAPAN MENGAJAR MAHASISWA PRODI PENDIDIKAN TEKNIK BANGUNAN - Rendi Wahyudi; Dr. Nurhasan Syah, M.Pd (Universitas Negeri Padang, 2019)
Abstract— This study aims to find out the relationship between the interest in being a teacher and teaching readiness. This type of research is quantitative correlational. This research was conducted in the Department of Civil Engineering, Faculty of Engineering, Padang State University. Informants / respondents in this study were students of the Building Engineering Education Study Program, Faculty of Engineering, Padang State University who had participated in the Educational Field Experience Program for the period July-December 2017 and the period January-June 2018. Data collection techniques in this study used questionnaires. While the Sampling Technique used is Random sampling. Random sampling technique is a data collection technique in whichtechniques are selected from the population. Reasons for taking random sampling because the population of 60 people is sufficient for trials and research so that the randomly selected population for the trial sample of 30 people was issued as the study sample, the study sample was taken from respondents who were not selected for the trial. The results of this study indicate that there is a significant relationship between the interest in being a teacher and teaching readiness of students in building engineering education. Keywords: Interest in Being a Teacher, Teaching Readiness